A* Variants for Optimal Multi-Agent Pathfinding - Goldenberg, Meir; Felner, Ariel; Stern, Roni; Schaeffer, Jonathan (Proceedings of the International Symposium on Combinatorial Search, 2012)
Several variants of A* have been recently proposed for find-ing optimal solutions for the multi-agent pathfinding (MAPF)problem. We describe the application of the new enhancedpartial-expansion technique to MAPF, show how patterndatabases can be applied on top of this technique and com-pare the different A* variants experimentally.